2022
DOI: 10.1186/s13195-022-00966-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide synthase inhibition reduces ganglioside GM3 accumulation, alleviates amyloid neuropathology, and stabilizes remote contextual memory in a mouse model of Alzheimer’s disease

Abstract: Background Gangliosides are highly enriched in the brain and are critical for its normal development and function. However, in some rare neurometabolic diseases, a deficiency in lysosomal ganglioside hydrolysis is pathogenic and leads to early-onset neurodegeneration, neuroinflammation, demyelination, and dementia. Increasing evidence also suggests that more subtle ganglioside accumulation contributes to the pathogenesis of more common neurological disorders including Alzheimer’s disease (AD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In a mouse model study, the reduction of G M3 ganglioside by inhibition of glucosylceramide synthase resulted in stabilized remote memory and lower soluble Aβ in the brain. 63 A previous human study showed that increased levels of the G M3 ganglioside species were associated with incident or prevalent AD. 8 Thus, our findings regarding these classes are in line with these reports, supporting the evidence for their potential roles in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…In a mouse model study, the reduction of G M3 ganglioside by inhibition of glucosylceramide synthase resulted in stabilized remote memory and lower soluble Aβ in the brain. 63 A previous human study showed that increased levels of the G M3 ganglioside species were associated with incident or prevalent AD. 8 Thus, our findings regarding these classes are in line with these reports, supporting the evidence for their potential roles in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…One recent study demonstrated alleviation of neuropathology in transgenic mice when treated with inhibitors within the GM3 pathway. 49 In the brain of male mice, total diacylglycerol pool was elevated, in contrast to the plasma where it was reduced. Diacylglycerol has been shown to be elevated in the frontal cortex of patients with AD, 50 , 51 however, why there is a sex difference and opposing results between plasma and brain in our model is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Venglustat had no apparent effects in the Y‐maze test and ameliorated an endophenotype in the NOR test, probably through reduction of a heightened anxiety‐like state in Thy1‐aSyn mice. This should raise caution regarding the interpretation of previously reported cognitive benefits in other PD, GD, or Alzheimer's disease models that could have been influenced by similar behavioral changes 12,13,44 . The apparent disparity between different behavioral domains (ie, motor and nonmotor) argues for brain region–specific effects of venglustat.…”
Section: Discussionmentioning
confidence: 99%
“…This should raise caution regarding the interpretation of previously reported cognitive benefits in other PD, GD, or Alzheimer's disease models that could have been influenced by similar behavioral changes. 12,13,44 The apparent disparity between different behavioral domains (ie, motor and nonmotor) argues for brain region-specific effects of venglustat. Indeed, venglustat tended to increase α-synuclein pathology and microgliosis in the SN of Thy1-aSyn mice but appeared to be neuroprotective in limbic brain regions, as reported previously in the hippocampus of PD/GD models.…”
Section: Discussionmentioning
confidence: 99%